PERTANGGUNGJAWABAN KEUANGAN PARTAI POLITIK MENUJU TATA KELOLA PARTAI POLITIK YANG BAIK - Yusuf Eko Nahuddin (Jurnal Cakrawala Hukum, 2015)
In the era of democracy, political parties have a role and function of constitutionally so dominant, even all leaders candikatan institution is the product of a political party.A political party is a major producer of public officials whoready on distribusikan in various positions in state institutions ranging from landscape president, a member of thehouse of representatives, the heads of the regions as well as various other strategic position. This position ensure asgovernment agencies are the authorities important in the policies concerning public interest.To transformed into amodern party political parties must make efforts the development of party management systems collectively especiallyin trouble financial management a vital organs in the management of party. In any activity kepartaian startofregeneration and no campaign finance regardless of who becomes the main factor of the success of the role andactivitiesof political parties.Because of that, to become a political party that modern cannot not must also be able toconductfinancial management with good.In the sense of starting from the source and the allocation of its financingintheir any activities. In connection with this required to the principles of transparency and accountability, so thatwhenon a management problem the financials for applied able to eliminate prejudice negatively on the party whorelyon the financial means only from a member of.However, this does not preclude the possibility of deviantbehaviorsa member of acts of corruption is the act of subverting. Of course it thereby will erode public confidence intheparty and it is certainly injurious of a party in his place as an organ of democracy nowadays.